The Duties of Sangging in the Implementation of the Hindu Religious Ceremony of Manusa Yadnya Metatah Mass in Bali: A Study of Occupational Health Science - Purnamawati , Made Sri Putri (South Eastern European Journal of Public Health, 2024)
Occupational Health and Safety (K3) is our effort to create a healthy and safe working environment, so that it can reduce the probability of work accidents / diseases due to negligence that result in demotivation and deficiencies in work productivity. According to the Basic Health Law of the Republic of Indonesia No. 9 of 1960 Chapter I Article II, Occupational Health is a health condition that aims for workers to obtain the highest level of health, both physical, spiritual and social, with prevention and treatment efforts for diseases or health disorders caused by work and the work environment or general diseases. in all work activities in human social and religious life such as research on mass metatah ceremonies that are often carried out by Hindus in Bali, in this case the position of the sangging is the key in this metatah ceremony. Sangging is a person who is tasked with cutting teeth during the metatah ceremony. The duties of the sangging in carrying out metatah are to sharpen the two canine teeth and four incisors in the upper jaw with a file. Providing toothpaste made from turmeric, betel lime and sandalwood rubbing. Following up on the Yama Pati Tatwa palm leaf, a sangging needs to understand the structure of tooth tissue and occupational health science to maintain the sanctity of the ceremony. The metatah ceremony or 'mepandes', 'mesangih' or 'metah ceremony' (Balinese) is a Hindu religious ceremony that must be carried out by all Hindus in Bali. The metatah ceremony contains meaning for life, namely changing behavior to become a true human being who can control himself from the temptation of lust, and fulfilling the obligations of parents to children in order to find the true nature of humanity. This study aims to analyze the nature of the implementation of the mass metatah ceremony in Bali Province in the study of occupational health science. The research design uses a case study based on its type, namely an explanatory case study, which focuses on the mass metatah ceremony. Data is analyzed descriptively and carefully until complete. The results of the study indicate that: 1) occupational health knowledge for the sangging in the mass metatah ceremony has the nature to achieve the maximum goal of the yadnya metatah ceremony, namely suppressing bad thoughts, words, and behavior by controlling themselves from the temptation of lust; 2) the process of implementing the metatah ceremony carried out by a sangging is done by filing both canine teeth and four jaw incisors. However, the process is carried out carefully according to health science and the impact of mass metatah, namely social, psychological, health and economic impacts. The implications of the research results, namely the implementation of the 'manusia yadnya' metatah must be carried out carefully by paying attention to health risks when the metatah ceremony is carried out, internence and application of occupational health science need to be carried out so that religious ceremonies become pure physically and mentally according to the purpose of the metatah ceremony.